Substrate properties of zebrafish Rtn4b/Nogo and axon regeneration in the zebrafish optic nerve. Issue 14 (23rd June 2017) - Bodrikov, Vsevolod; Welte, Cornelia; Wiechers, Marianne; Weschenfelder, Markus; Kaur, Gurjot; Shypitsyna, Aleksandra; Pinzon‐Olejua, Alejandro; Bastmeyer, Martin; Stuermer, Claudia A. O.
Abstract: This study explored why lesioned retinal ganglion cell (RGC) axons regenerate successfully in the zebrafish optic nerve despite the presence of Rtn4b, the homologue of the rat neurite growth inhibitor RTN4‐A/Nogo‐A. Rat Nogo‐A and zebrafish Rtn4b possess characteristic motifs (M1‐4) in the Nogo‐A‐specific region, which contains delta20, the most inhibitory region of rat Nogo‐A. To determine whether zebrafish M1‐4 is inhibitory as rat M1‐4 and Nogo‐A delta20, proteins were recombinantly expressed and used as substrates for zebrafish single cell RGCs, mouse hippocampal neurons and goldfish, zebrafish and chick retinal explants. When offered as homogenous substrates, neurites of hippocampal neurons and of zebrafish single cell RGCs were inhibited by zebrafish M1‐4, rat M1‐4, and Nogo‐A delta20. Neurite length increased when zebrafish single cell RGCs were treated with receptor‐type‐specific antagonists and, respectively, with morpholinos (MO) against S1PR2 and S1PR5a—which represent candidate zebrafish Nogo‐A receptors. In a stripe assay, however, where M1‐4 lanes alternate with polylysine‐(Plys)‐only lanes, RGC axons from goldfish, zebrafish, and chick retinal explants avoided rat M1‐4 but freely crossed zebrafish M1‐4 lanes—suggesting that zebrafish M1‐4 is growth permissive and less inhibitory than rat M1‐4. Moreover, immunostainings and dot blots of optic nerve and myelin showed that expression of Rtn4b is very low in tissue and myelin at 3–5 days after lesion when axons regenerate. Thus, Rtn4b seems to represent no major obstacle for axon regeneration in vivo because it is less inhibitory for RGC axons from retina explants, and because of its low abundance. Abstract : Rtn4b (red), the zebrafish homologue of rat Nogo‐A/RTN4‐A, exists in only very small amounts in myelin debris of the lesioned optic nerve so that growth cones regrow and axons regenerate. Rat CNS myelin, by contrast, has abundant Nogo‐A/RTN4‐A (red) which blocks growth and causes growth cone retraction.